Discovery of a Series of 1,2,3-Triazole-Containing Erlotinib Derivatives With Potent Anti-Tumor Activities Against Non-Small Cell Lung Cancer - Sun, Ge; Mao, Longfei; Deng, Wenjing; Xu, Shuxiang; Zhao, Jie; Yang, Jianxue; Yao, Kaitai; Yuan, Miaomiao; Li, Wei (Frontiers in Chemistry, 2022)
Epidermal growth factor receptor （EGFR）tyrosine kinase inhibitors (TKIs) are emerging at the vanguard of therapy for non-small-cell lung cancer (NSCLC) patients with EGFR-activating mutations. However, the increasing therapeutic resistance caused by novel mutations or activated bypass pathways has impaired their performance. In this study, we link one of the commercial EGFR-TKIs, Erlotinib, to different azide compounds to synthesize a novel class of 1,2,3-triazole ring-containing Erlotinib derivatives. We discovered that several new compounds show robust antiproliferation activity against diverse NSCLC cells in vitro including PC-9, H460, H1975 and A549. Two of the most potent compounds, e4 and e12 have been found to be more efficient than Erlotinib in all NSCLC cell lines except PC-9. They significantly induce apoptosis and cell cycle arrest in PC-9 and H460 cells. The antitumor efficacy of compound e4 in vivo is close to that of Erlotinib in a PC-9 xenograft mouse model. Most Erlotinib-1,2,3-triazole compounds exhibit moderate to good inhibitory activities toward wild-type EGFR as indicated by enzyme-linked immunosorbent assay (ELISA), and the EGFR phosphorylation was inhibited in H460 and PC-9 cells exposed to e4 or e12. These data suggest that these Erlotinib-1,2,3-triazole compounds are suitable candidates for use against NSCLC and more unknown mechanisms merit further investigation.